A study on methods and classification conditions for building facade materials - Tay, Hui Xin (Nanyang Technological University, 2020)
Artificial Intelligence (AI) has been a popular topic in this age of technology. In the construction industry, it plays an vital role in improving the productivity and efficiency of work. This paper focuses on the development of an automated crack detection system using AI technology. The purpose is to improve the façade inspection and to increase the effectiveness in image analysis of defects. In the proposed method, classification and segmentation models are used to detect the presence of defects on building facades. The scope covers cracking and spalling on building facades in Singapore. Overall the result of the automated crack detection system developed achieves good performance with high accuracy result. To conclude, this is a significant finding in the construction field for future development and enhancement.